CHRONOLOGY AND TECTONIC FRAMEWORK OF TURBIDITE-HOSTED GOLD DEPOSITS IN THE WESTERN LACHLAN FOLD BELT, VICTORIA: - Foster D.A.; Gray D.R.; Kwak T.A.P.; Bucher M. (My University, 1998)
40Ar-39Ar data constrain the history of metamorphism, deformation and mineralization in the western subprovince of the Lachlan Fold Belt. Rocks in the Mount Stavely Volcanic Complex and the Bushy Creek Pluton give 40Ar-39Ar ages of about 500 Ma for hornblende and biotite. The dates from the Mount Stavely Volcanic Complex limit the age of mineralization in the metavolcanic rocks of the Stavely Belt. Whereas, the date for the Bushy Creek pluton extends the area of Cambrian-Ordovician plutons, of the Delamerian Orogeny, to east of the Grampians Mountains and helps define the surface expression of the western border of the Paleozoic Lachlan Fold Belt. 40Ar-39Ar dating of metamorphic mica growth (phengite) in cleaved slates and phyllites within the Landsborough Fault, Avoca Fault zone, Heathcote Fault zone and Mount Wellington Fault zone gives ages of 453+/-2, 440+/-2, 426+/-4 and 410-390 Ma, respectively. These data indicate a progression of deformation from west to east starting in Late Ordovician-Early Silurian time in the Stawell and Bendigo-Ballarat structural zones. The major phase of deformation in the western subprovince of the Lachlan Fold Belt is therefore Silurian and not Devonian. Sericites from major gold deposits in the Stawell zone and Bendigo-Ballarat zone give 40Ar-39Ar dates of about 440 Ma, that are coincident with folding and thrusting. A second episode of mineralization and fault reactivation at about 420 to 410 Ma is found in some deposits in these zones, based on data from a previous study. In the Melbourne zone (including the Woods Point Dike Swarm) and locally in the Bendigo-Ballarat zone, some gold deposits give sericite dates of about 380-360 Ma. These ages are consistent with the close association of many Melbourne zone gold deposits with Devonian dikes and plutons.The results indicate that gold mineralization in the Stawell zone, Bendigo-Ballarat zone and Melbourne zone was episodic and both temporally and spatially associated with crustal heating linked to regional metamorphism and plutonism. Initial stages of mineralization in the province, comprising many of the large deposits in western and central Victoria (e.g. Bendigo, Ballarat, Stawell, Wattle Gully, Tarnagulla), accompanied metamorphism, folding and thrusting. Subsequent mineralization is widespread but produced mainly smaller deposits (<10,000 kg, with the exception of Walhalla-Woods Point) and was associated with the thermal events accompanying Devonian dike and pluton intrusion and deformation.
Keywords: TURBIDITE-HOSTED; GOLD MINERALISATION; GEOCHRONOLOGY; 40AR-39AR; LACHLAN FOLD BELT; AUSTRALIA